PENGARUH PAJAK HIBURAN, PAJAK RESTORAN, DAN PAJAK HOTEL TERHADAP PENDAPATAN ASLI DAERAH KOTA BATU (Studi Kasus Badan Keuangan Daerah Kota Batu Tahun 2016-2018) - Ade Sistiayu N; Jeni Susyanti; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT The purpose of this study are: 1) To analyze the effect of Hotel Taxes on the Original Revenue of the City of Batu, 2) To analyze the effect of Restaurant Taxes on the Regional Revenue of Batu City, 3) To analyze the influence of Entertainment Taxes on the Regional Revenue of Batu City. The object used in this study is the Regional Revenue of Batu City originating from Hotel Taxes, Restaurant Taxes, and Entertainment Taxes and obtained in 2016-2018. Based on this study, it shows that here the Hotel Tax has a significant effect on the Regional Original Income of Batu, which shows the results of the Hotel Tax significance value of 0.007. The analysis of this study shows that the Tax of Hotels in Batu City has an influence on the Regional Revenue of Batu City. Restaurant Tax has a significant effect on the Regional Original Income of Batu City in 2016-2018, which shows the results of the Restaurant Tax significance value of 0.001. This analysis shows that the Restaurant Tax in Batu City has an influence on the Regional Revenue of Batu City. Entertainment Tax has a significant influence on the Regional Original Income of Batu City in 2016-2018, which shows the results of the Entertainment Tax significance value of 0.022. This analysis shows that Entertainment Tax has an influence on the Regional Revenue of Batu City.Keywords: Hotel Tax, Restaurant Tax, Entertainment Tax, Regional Original Income